2012
DOI: 10.1111/j.1758-5910.2011.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid NOTES colectomy for right‐sided colonic tumors

Abstract: The operation was performed on a 42-year-old woman and lasted 120 minutes; blood loss was 30 mL. The patient had an uneventful recovery and was discharged on postoperative day 5. The median pain score was 2 (range, 2-3). Our preliminary experience shows that hybrid NOTES right hemicolectomy is safe and feasible. The technique eliminates the need for mini-laparotomy in patients undergoing laparoscopic right hemicolectomy, and it offers promise in this era of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…While single‐incision laparoscopic resections may improve recovery, no robust data have yet appeared and these techniques are at an early stage in their development . Furthermore, transvaginal and transrectal specimen extraction to avoid abdominal wounds has been described, but with little data on short‐ and long‐term results . At this stage, no recommendation can be made on these procedures.…”
Section: Part B Intraoperative and Postoperative Eras Elementsmentioning
confidence: 99%
“…While single‐incision laparoscopic resections may improve recovery, no robust data have yet appeared and these techniques are at an early stage in their development . Furthermore, transvaginal and transrectal specimen extraction to avoid abdominal wounds has been described, but with little data on short‐ and long‐term results . At this stage, no recommendation can be made on these procedures.…”
Section: Part B Intraoperative and Postoperative Eras Elementsmentioning
confidence: 99%
“…Natural orifice specimen extraction (NOSE) is a method that can achieve specimen extraction from natural orifices (transvaginal, transanal, transrectal, transcolonic) [8]. Recently, several studies have confirmed the safety and feasibility of laparoscopic resection with NOSE for the treatment of colorectal disease [9][10][11][12][13][14][15]. However, conflicting conclusions stating that NOSE may increase the possibility of peritoneal contamination have also been yielded [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Coloshield may serve as an effective colon occlusion device during transrectal NOTES. It may contribute towards development of transrectal hybrid-NOTES in abdominal organs that are remote from the rectum such as cholecystectomy [7], prostatectomy [22], nephrectomy [23,24], or right sided colectomy [25]. Rectal washout with povidone reduced the contamination of the rectal wall and peritoneum in left colic resection (10).…”
Section: Discussionmentioning
confidence: 99%